Implementasi Pembelajaran E-Learning Pada Kelas Praktikum (Studi Kasus : Universitas Madura) - Nindian Puspa Dewi; Nanik Winarsih (Jurnal Komputer Terapan, 2020)
E-learning is a container that handles online learning systems that can be accessed anywhere by utilizing internet access. Practicum is one of the activities to improve the understanding of theory by carrying out trials or exercises in accordance with the subjects taught, so that e-learning in question can be used as a container that can be used by practicum lecturers and students in handling the activities of prakitkum activities at the University Informatics Engineering Laboratory Madura In this research, an e-learning is made that can handle practical activities, such as managing assignments, making modules, conducting online exams, and discussions that are built using ionic and native php programming languages.